When should axillary drains be removed post axillary dissection? A systematic review of randomised control trials. - Kelley, T; Thomson, DR; Furniss, D (2012)
OBJECTIVE: To determine the evidence-based optimal strategy for management of drains following axillary dissection. BACKGROUND: Despite randomised control trials addressing the issue over the past 20-30 years, there is no widely accepted consensus as to when drains should be removed post axillary dissection. METHODS: We searched the electronic databases Medline, Embase, Cinahl, Cochrane Library of Systematic Reviews and Web of Science Citation Index. References within identified studies were also searched. Studies were independently identified and data extracted according to a pre-determined proforma based on the Cochrane Collaboration data extraction template by two independent researchers. Validity was determined according to a published standard. Discrepancies were corrected by consensus. RESULTS: There was no difference in infection rates between early and late drain removal, hospital stay was reduced when drains were removed earlier, and higher total volume drainage prior to drain removal predicted subsequent seroma formation. The optimal timing of drain removal post axillary dissection could not be determined from the literature. CONCLUSION: Optimal timing of drain removal following axillary dissection remains unknown after this systematic review due to heterogeneity between included studies leading to an inability to provide evidence-based consensus guidance.